Functional Quality of Service During Events: An Empirical Analysis (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
Visitors to events attach great importance to the range of artists and their performances and the quality of their stay and services. To create a staging and, consequently, an emotionalization of the visitor, many action areas simultaneously take effect at an event. In this context, the customer satisfaction of visitors plays a major role for event organizers, which aims to generate a competitive advantage over other providers and be attractive for artists simultaneously. This article aims to analyse the perceived functional quality of service (QoS) during various events in a multi-purpose event venue. The analysis was based on 563 primary data samples. On the off chance, selected visitors were during the events recruited and interviewed using a standardized questionnaire. The data were collected during the break of five events. These events took place in the period from mid-November to mid-December 2019. This was supplemented by an online survey of enthusiastic fan club visitors who regularly watch handball matches within the event venue. The online survey was conducted in parallel with the surveys during November 2019. Overall, the results showed a high level of satisfaction among visitors regarding the QoS. In addition to services, exploratory factor analysis identified cleanliness as a satisfaction factor that significantly accounted for overall service satisfaction. Differences in the perception of both factors could be detected between the fan club visitors on the one hand and all other visitors of various events (comedy, music, sports) on the other. Based upon the results of this analysis, the event managers of this venue are enabled to employ target group-oriented improvements of individual services to consolidate and increase customer satisfaction.